2015
DOI: 10.5194/acp-15-5275-2015
|View full text |Cite
|
Sign up to set email alerts
|

Data assimilation of satellite-retrieved ozone, carbon monoxide and nitrogen dioxide with ECMWF's Composition-IFS

Abstract: Daily global analyses and 5-day forecasts are generated in the context of the European Monitoring Atmospheric Composition and Climate (MACC) project using an extended version of the Integrated Forecasting System (IFS) of the European Centre for Medium-Range Weather Forecasts (ECMWF). The IFS now includes modules for chemistry, deposition and emission of reactive gases, aerosols, and greenhouse gases, and the 4-dimensional variational data assimilation scheme makes use of multiple satellite observations of atmo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
146
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(162 citation statements)
references
References 91 publications
(18 reference statements)
3
146
0
3
Order By: Relevance
“…1) which leads to increased wet deposition and removal of aerosols, while not removing the gas-phase species in the same way. Inness et al, 2015).…”
Section: Enso Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…1) which leads to increased wet deposition and removal of aerosols, while not removing the gas-phase species in the same way. Inness et al, 2015).…”
Section: Enso Anomaliesmentioning
confidence: 99%
“…A basic initial validation of C-IFS fields can be found in Flemming et al (2015) and Inness et al (2015) and more detailed validation of C-IFS can be found in the validation reports available from http://www.copernicus-atmosphere.eu/. The chemistry scheme implemented in the C-IFS model version used for these experiments is an extended, modified version of the Carbon Bond Mechanism 5 (Yarwood et al, 2005) chemical mechanism as originally implemented in the chemistry transport model TM5 (Tracer Model 5) (Huijnen et al, 2010;Williams et al, 2013;Huijnen et al, 2014).…”
Section: Atmosmentioning
confidence: 99%
“…Global chemical data assimilation (e.g., Inness et al, 2015;Miyazaki et al, 2015) and emission inversion (e.g., Stavrakou et al, 2013;Miyazaki et al, 2017) would also benefit from high-resolution global CTMs through improvements in model performance (e.g., Arellano Jr. et al, 2007) and reduced spatial representation gaps between observed and simulated fields. Several previous studies (Mijling and van der A, 2012;Ding et al, 2017b;Liu et al, 2017) demonstrated the importance of high-resolution modeling in detecting small-scale NO x emission sources such as urban, new power plant, and ship emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The background color code shows annual CO 2 emissions for the year 2013 as extracted from the database built by Oda and Maksyutov (2011). ing services such as developed within the European Copernicus programme (e.g. Inness et al, 2015).…”
Section: A Butz Et Al: Geostationary Emission Explorer For Europe (mentioning
confidence: 99%